Analisis Kesesuaian Materi Klasifikasi Tumbuhan Pada Buku Teks SMA Kelas X - Anggraini Eka Putri; Tri Jalmo; Arwin Surbakti (Universitas Lampung, 2018)
This study aim was to describe the conformity level of Plant Classification materials on biology textbooks with basic competence from aspect material breadth and depth. This research was a qualitative research using documentation study. The samples was used A book and B book. The instrument of this research was the material conformity sheet in terms of the material breadth and depth. Data collection through documentation study by analyzing content of material. The data of this research were analyzed descriptively qualitative. The result of the conformity analysis of book material A and B in terms of the breadth of material shows the category